Backside‐illuminated scientific CMOS detector for soft X‐ray resonant scattering and ptychography. (26th October 2020) - Desjardins, Kewin; Medjoubi, Kadda; Sacchi, Maurizio; Popescu, Horia; Gaudemer, Roland; Belkhou, Rachid; Stanescu, Stefan; Swaraj, Sufal; Besson, Adrien; Vijayakumar, Jaianth; Pautard, Stéphanie; Noureddine, Arafat; et al.
Abstract : This paper reports measurement results and an experimental demonstration of a new backside‐illuminated scientific CMOS sensor for soft X‐ray experiments at the SOLEIL synchrotron. Abstract : The impressive progress in the performance of synchrotron radiation sources is nowadays driven by the so‐called `ultimate storage ring' projects which promise an unprecedented improvement in brightness. Progress on the detector side has not always been at the same pace, especially as far as soft X‐ray 2D detectors are concerned. While the most commonly used detectors are still based on microchannel plates or CCD technology, recent developments of CMOS (complementary metal oxide semiconductor)‐type detectors will play an ever more important role as 2D detectors in the soft X‐ray range. This paper describes the capabilities and performance of a camera equipped with a newly commercialized backside‐illuminated scientific CMOS (sCMOS‐BSI) sensor, integrated in a vacuum environment, for soft X‐ray experiments at synchrotron sources. The 4 Mpixel sensor reaches a frame rate of up to 48 frames s −1 while matching the requirements for X‐ray experiments in terms of high‐intensity linearity (>98%), good spatial homogeneity (<1%), high charge capacity (up to 80 ke − ), and low readout noise (down to 2 e − r.m.s.) and dark current (3 e − per second per pixel). Performance evaluations in the soft X‐ray range have been carried out at the METROLOGIE beamline of the SOLEIL synchrotron. The quantum efficiency, spatial resolution (24 line‐pairs mm −1 ), energy resolution (<100 eV) and radiation damage versus the X‐ray dose (<600 Gy) have been measured in the energy range from 40 to 2000 eV. In order to illustrate the capabilities of this new sCMOS‐BSI sensor, several experiments have been performed at the SEXTANTS and HERMES soft X‐ray beamlines of the SOLEIL synchrotron: acquisition of a coherent diffraction pattern from a pinhole at 186 eV, a scattering experiment from a nanostructured Co/Cu multilayer at 767 eV and ptychographic imaging in transmission at 706 eV.